Probabilistic prediction of cavitation on rotor blades of tidal stream turbines. (December 2017) - Chernin, Leon; Val, Dimitri V.
Abstract: Power generation from tidal currents is currently a fast developing sector of the renewable energy industry. A number of technologies are under development within this sector, of which the most popular one is based on the use of horizontal axis turbines with propeller-type blades. When such a turbine is operating, the interaction of its rotating blades with seawater induces pressure fluctuations on the blade surface which may cause cavitation. Depending on its extent and severity, cavitation may damage the blades through erosion of their surface, while underwater noise caused by cavitation may be harmful to marine life. Hence, it is important to prevent cavitation or at least limit its harmful effects. The paper presents a method for predicting the probability of cavitation on blades of a horizontal axis tidal stream turbine. Uncertainties associated with the velocities of seawater and water depth above the turbine blades are taken into account. It is shown how using the probabilistic analysis the expected time of exposure of the blade surfaces to cavitation can be estimated. Highlights: A probabilistic approach to predicting the cavitation on the rotor blades of a tidal stream turbine is proposed. Probabilistic models describing uncertainties associated with seawater velocities and depth above blades are introduced. A case study illustrating the application of new probabilistic approach and existing deterministic approach is presented. Probabilistic approach is found advantageous for rational and economically efficient cavitation design of blades.